Feasibility Study for Developing an Event Prioritizing System Using CMSs - Hussein, Abdullah; Mohamed , Rozlina (International Journal of Intelligent Systems and Applications in Engineering, 2023)
A content management system (CMS) is software that lets users make, modify, publish, and save digital information. These systems provide a piece of software called a plugin, model, or extension that plugs into users' sites and add new functionality or extends existing functionality on the user site. In current events, prioritization is done manually. When changes in event attributes like personnel, logistics, or money happen after the hand-prioritized list of activities is completed, it is not an easy task to reprioritize. By developing an event prioritization plugin, the organizations in need will use it and reduce time and money consumption. This study aims to recognize and evaluate the existing CMSs, their domains, and available plugins. Assess the availability of event prioritization plugins and recommend developing a plugin to help charity organizations to select the best team and resources and conduct the events effectively. The search is done in the area of the developed research questions. Search phrases containing pertinent keywords were used to find primary studies linked to CMSs categorized under journal articles, conference papers, seminars, symposiums, book chapters, and related CMSs websites.